Is tofacitinib a game‐changing drug for ulcerative colitis?. Issue 7 (1st August 2020) - Magro, Fernando; Estevinho, Maria Manuela
Abstract : The increasing knowledge on ulcerative colitis' pathophysiology has contributed to the expansion of the therapeutic arsenal for this condition. However, to date, 25–40% of patients with ulcerative colitis remain primary or secondary non‐responders to therapy, and up to 10% need to eventually undergo a colectomy. Janus kinase inhibitors block cytokine signalling involved in the pathogenesis of several inflammatory conditions. Tofacitinib is the first drug of this class approved for moderate‐to‐severely active ulcerative colitis in patients for whom disease worsened and those who did not improve with conventional therapy (aminosalicylates, corticosteroids and immunosuppressants) or monoclonal antibodies. We aimed to review the main aspects and concerns related to the current use of tofacitinib and to explore its future application.